The missing grains in Madura foot: imaging to the rescue - V. P. K., Gopinath; C. M., Ali Rishad; P. M., Farisa (International Journal of Research in Dermatology, 2018)
Mycetoma or Madura foot is a chronic localized granulomatous infection caused by varied species of fungi or actinomycetes clinically diagnosed by active discharging sinuses containing ‘grains’. In atypical presentations or patients unwilling for invasive investigations, imaging essentially plays a key role in diagnosis and helps to differentiate actinomycetoma from eumycetoma. Here we present such an atypical case of unilateral foot swelling without sinuses–cryptic mycetoma. This 69 year old male from Kerala had a swelling over the left foot following trauma initially painless. An x-ray taken showed normal underlying bones with mild soft tissue swelling. To evaluate further USG was taken which showed fine hyperechoiec foci settled at the bottom of cavities highly suggestive of mycetoma. For confirmation USG guided biopsy was taken but was inconclusive. As patient was not willing for repeat biopsy, we advised non invasive MRI that revealed classical ‘Dot In Circle’ sign specific for mycetoma. The distinction that makes the case stand out is its absence of classical picture of discharging sinuses and the fact that imaging rather than histopathology helped confirm the diagnosis in mycetoma.